2-O-Benzhydryl-3,4-(S)-O-benzyl-idene-d-xylono-1,4-lactone. - Jenkinson, S; Rule, S; Booth, K; Fleet, G; Watkin, D; Petursson, S (2008)
X-ray crystallography unequivocally shows that protection of the free hydroxyl group of 3,5-O-benzyl-idene-d-xylono-1,4-lactone with diphenyl-diazo-methane proceeded smoothly to give the title compound, C(25)H(22)O(5), with no accompanying epimerization. Unlike the analogously protected lyxono lactone, the isomeric xylono lactone has two mol-ecules present in the asymmetric unit (Z' = 2). The 5-ring lactones adopt envelope conformations and the 6-ring ketals adopt chair conformations.